2019
DOI: 10.1111/cea.13489
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of recombinant Bacillus subtilis spores expressing Helicobacter pylori neutrophil‐activating protein suppresses peanut allergy via up‐regulation of Tregs

Abstract: Background Helicobacter pylori neutrophil‐activating protein (NAP) is an immune modulator with anti‐Th2 inflammation activity that can be used to prevent IgE‐mediated allergic reactions. Cholera toxin B (CTB) is a mucosal adjuvant that can induce antigen tolerance. Bacillus subtilis spores are an ideal vehicle for the oral delivery of heterologous antigens. Objective We investigated the therapeutic effect of recombinant NAP B subtilis spores on peanut allergies in a mouse model. Methods Female C3H/HeJ mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In this study, C3H/HeJ mice showed extensive reactions, such as increased IgE, IgG1, and mMCP-1, and Th2-associated cytokine levels, decreased Treg populations in immune tissues, as well as decreased body temperature after OVA treatment without adjuvant. In previous researches, similarly, the C3H/HeJ strain mice also displayed obvious humoral immune reactions, cellular immune responses, and systemic allergy symptoms to ovomucoid (OM) (39), peanut (40)(41)(42), and fish allergens (43) by oral administration combined with cholera toxin (CT). The route and mechanism of CT influencing the intestine might be the same as those by which some bacteria act on the intestinal barrier, although the CT is not involved in the pathogenesis of food allergy itself (44,45).…”
Section: Discussionmentioning
confidence: 92%
“…In this study, C3H/HeJ mice showed extensive reactions, such as increased IgE, IgG1, and mMCP-1, and Th2-associated cytokine levels, decreased Treg populations in immune tissues, as well as decreased body temperature after OVA treatment without adjuvant. In previous researches, similarly, the C3H/HeJ strain mice also displayed obvious humoral immune reactions, cellular immune responses, and systemic allergy symptoms to ovomucoid (OM) (39), peanut (40)(41)(42), and fish allergens (43) by oral administration combined with cholera toxin (CT). The route and mechanism of CT influencing the intestine might be the same as those by which some bacteria act on the intestinal barrier, although the CT is not involved in the pathogenesis of food allergy itself (44,45).…”
Section: Discussionmentioning
confidence: 92%
“…Its abundance was reduced in the gut microbiota of colitis mice but recovered following anti-inflammatory therapy [ 55 ]. Helicobacteraceae shows beneficial effects against food allergy, for instance, the neutrophil-activating protein of Helicobacter pylori can inhibit peanut allergy by up-regulating the production of Tregs [ 56 ]. The level of Bacillaceae is related to gut inflammatory diseases [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The recombinant plasmid was sequenced and transformed into B. subtilis WB600 cells. Sporulation of recombinant B. subtilis was induced via Difco sporulation medium (DSM) as previously described (Mai et al 2019 ). Spores were centrifuged at 8000 × g for 15 min, and the supernatant was removed.…”
Section: Methodsmentioning
confidence: 99%